A Call to Action: A Specialty-Specific Course to Support the Next Generation of Clinician Scientists in Anesthesiology. (15th September 2022) - Cavallone, Laura F.; Duggan, Elizabeth W.; Berger, Jeffrey S.
Abstract : Clinical production pressure is a significant problem for faculty of anesthesiology departments who seek to remain involved in research. Lack of protected time to dedicate to research and insufficient external funding add to this long-standing issue. Recent trends in funding to the departments of anesthesiology and their academic output validate these concerns. A 2022 study examining National Institutes of Health (NIH) grant recipients associated with anesthesiology departments across 10 years (2011–2020) outlines total awarded funds at 1, 676, 482, 440, with most of the funds awarded to only 10 departments in the United States. Of note, the total 1-year NIH funding in 2021 for academic internal medicine departments was 3 times higher than the 10-year funding of anesthesiology departments. Additionally, American Board of Anesthesiology (ABA) diplomats represent a minority (37%) of the anesthesiology researchers obtaining grant funding, with a small number of faculty members receiving a prevalence of monies. Overall, the number of publications per academic anesthesiologist across the United States remains modest as does the impact of the scholarly work. Improving environments in which academic anesthesiologists thrive may be paramount to successful academic productivity. In fact, adding to the lack of academic time is the limited bandwidth of senior academic physicians to mentor and support aspiring physician scientists. Given then the challenges for individual departments and notable successes of specialty-specific collaborative efforts (eg, Foundation for Anesthesia Education and Research [FAER]), additional pooled-resource approaches may be necessary to successfully support and develop clinician scientists. It is in this spirit that the leadership of Anesthesia & Analgesia and The Journal of Education in Perioperative Medicine, unified with the Association of University Anesthesiologists, aim to sponsor the Introduction to Clinical Research for Academic Anesthesiologists (ICRAA) Course. Directed toward early career academic anesthesiologists who wish to gain competency specifically in the fundamentals of clinical research and receive mentorship to develop an investigative project, the yearlong course will provide participants with the skills necessary to design research initiatives, ethically direct research teams, successfully communicate ideas with data analysts, and write and submit scientific articles. Additionally, the course, articulated in a series of interactive lectures, mentored activities, and workshops, will teach participants to review articles submitted for publication to medical journals and to critically appraise evidence in published research. It is our hope that this initiative will be of interest to junior faculty of academic anesthesiology departments nationally and internationally.